ANALISIS KELEMBAGAAN PENGELOLAAN SUMBERDAYA IKAN DI PESISIR TANJUNG ULAR KABUPATEN BANGKA BARAT - ENDANG BIDAYANI (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2010)
Tin production in Kabupaten Bangka Barat (Bangka Belitung Province) generated positive and negative impact to environment. The aim of this research is to analyze institutional of illegal mining (TI) activity to fisherman in Tanjung Ular Coastal area, Kabupaten Bangka Barat. The data was analyzed by the method institutional analysis. The result show that conflict caused by open access regime management. The policy of fishery sector development is alternative policy from government and stake holders